Research on architecture and algorithm for code resolution system in the internet of things - Hai-ning YU; Hong-li ZHANG; Bin-xing FANG; Xiang-zhan YU (Tongxin xuebao)
Based on a list of requirements for code resolution,a code resolution system architecture that is a distributed system of independent,collaborating code resolution services was presented.Meanwhile,an improved SkipNet based code resolution service named SkipNet-OCRS was proposed.It not only inherits DHT’s traditional advantages,but also supports administrative control and autonomy.Simulation experiments verify the excellent performance of SkipNet-OCRS.